2019
DOI: 10.3389/fpls.2019.01508
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Traits for Shortening Crop Duration and Improving Productivity of Greengram (Vigna radiata L. Wilczek) Under High Temperature

Abstract: Greengram is an important protein-rich food legume crop. During the reproductive stage, high temperatures cause flower drop, induce male sterility, impair anthesis, and shortens the grain-filling period. Initially, 116 genotypes were evaluated for 3 years in two locations, and based on flowering, biomass, and yield attributes, they were grouped into four major clusters. A panel of 17 contrasting genotypes was selected for their heat tolerance in high-temperature greenhouses. The seedlings of the selected genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 104 publications
(110 reference statements)
0
25
0
Order By: Relevance
“…In SuSy-impaired mutants of species in question, no developmental delay has been reported so far, presumably due to the redundancy of individual SUS genes [174]. However, the earlier onset of SuSy activity was reported in thermotolerant, rapidly maturing accessions of greengram (Vigna radiata) [175]. In addition, the prolonged pre-storage phase in ap2 mutants of Arabidopsis was shown to correlate with the elevated hexose/sucrose ratio [100].…”
Section: Metabolic Control Of Seed Developmentmentioning
confidence: 96%
See 1 more Smart Citation
“…In SuSy-impaired mutants of species in question, no developmental delay has been reported so far, presumably due to the redundancy of individual SUS genes [174]. However, the earlier onset of SuSy activity was reported in thermotolerant, rapidly maturing accessions of greengram (Vigna radiata) [175]. In addition, the prolonged pre-storage phase in ap2 mutants of Arabidopsis was shown to correlate with the elevated hexose/sucrose ratio [100].…”
Section: Metabolic Control Of Seed Developmentmentioning
confidence: 96%
“…The increased rates of seed filling at higher temperatures were demonstrated to be related to nitrogen uptake and remobilization in P. sativum [34]. In V. radiata, both higher ambient temperature and reduced photoperiod were found to accelerate seed maturation at the cost of seed size and nutrient composition in thermosusceptible accessions [175]. This effect was not observed in thermotolerant accessions with stable high seed yields, presumably due to early sucrose synthase activation and enhanced production of Hsp101 molecular chaperones [175].…”
Section: Environmental Factors Affecting Seed Development Ratementioning
confidence: 98%
“…Exposure to drought stress alters various morpho-physiological functions like change in flowering time, maturity duration, plant architecture, pod number, seed weight, stomatal conductance, relative water content (RWC), leaf and canopy temperature, transpiration rate and chlorophyll content [72,73]. Abiotic stresses also induce anthesis and shorten the reproductive phase in the mungbean [15]. Several kinds of research have demonstrated ample genetic variations among key traits that confer drought tolerance (Table 2).…”
Section: Morpho-physiological Trait Variations For Improving Drought Tolerancementioning
confidence: 99%
“…It is an excellent source of vegetable proteins, micro-nutrients and antioxidants like flavonoids and phenolics [9][10][11] and has multifarious uses as a food [12,13], feed, fodder [14] and green manure crop. Despite being an economically important crop, the productivity of mungbean is stagnant due to erratic weather conditions coupled with various biotic and abiotic stresses [15,16]. Among the abiotic stresses, drought is the most limiting factor for mungbean cultivation that hampers its growth and yield.…”
Section: Introductionmentioning
confidence: 99%
“…At high temperature flower drop, induce male sterility to impair anthesis and shorten grain filling period at reproductive stage. Two different genotypes EC 398889 and LGG 460 were identified which were heat tolerance and heat sensitive at temperature range 37-52 0 C and also sucrosesynthase activity and pollen germination were normal at a temperature beyond 40 0 C in EC 398889 than LG 460 (Basu et al, 2019) [11] . Aboitic stresses are adversely affected green gram adaptability and productivity including heat, drought, salinity and water-logging, which affect crop growth and development by altering physiological process and the plantwater relationship (Suzuki et al 2014;Zandalinas et al, 2017;Landi et al, 2017) [54,62,25] .…”
Section: Impact Of Heat Stress On Moongmentioning
confidence: 99%